Clothing terminology at Sv. Trojica in Slovenske gorice - Koletnik, Mihaela; Gungl, Benedikta (Slavia Centralis, 2022)
The article deals with previously unrecorded dialect terms for clothing, mainly of Slavic origin, gathered at Sveta Trojica in Slovenske gorice. In this even today predominantly rural area in the heart of Slovenske gorice, work clothes and festive garments, headgear and footwear of peasants and other villagers were provided by various village and market artisans. Alongside weavers, these were mainly tailors and cobblers, while professional seamstresses were instead prohibited from starting their own business before the 19th century, namely until the adoption of the craft order in 1859. The Trojica speech, which preserves quantitative contrasts, forms part of the Slovenske gorice dialect of the Pannonian dialect group. The dialect terms, presented in the form of 112 alphabetically arranged dictionary entries, are organised based upon their expressive image, illuminated in light of their etymological characteristics, and defined in terms of word class.